Morphological and phylogenetic analyses reveal two new Penicillium species isolated from the ancient Great Wall loess in Beijing, China - Liang, Ruina; Yang, Qiqi; Li, Ying; Yin, Guohua; Zhao, Guozhu (Frontiers in Microbiology, 2024)
Penicillium species exhibit a broad distribution in nature and play a crucial role in human and ecological environment. Two Penicillium species isolated from the ancient Great Wall loess in Mentougou District of Beijing, China, were identified and described as new species, namely Penicillium acidogenicum and P. floccosum, based on morphological characteristics and phylogenetic analyses of multiple genes including ITS, BenA, CaM and RPB2 genes. Phylogenetic analyses showed that both novel species formed a distinctive lineage and that they were most closely related to P. chrzaszczii and P. osmophilum, respectively. Penicillium acidogenicum is characterized by biverticillate conidiophores that produce globose conidia, and is distinguished from similar species by its capacity to grow on CYA at 30 °C. Penicillium floccosum is typically recognized by its restricted growth and floccose colony texture. The description of these two new species provided additional knowledge and new insights into the ecology and distribution of Penicillium.